Construcción del Derecho de las Audiencias: el Caso de las Defensorías del Televidente en Colombia - Restrepo-Yepes, Olga Cecilia; Molina-Saldarriaga, César Augusto; Restrepo-Yepes, Juan Diego; Bedoya-Taborda, Luisa Fernanda; Palacio-Mesa, Rubén Dario (Law, State and Telecommunications Review, 2022)
[Purpose] To analyze the construction of the objective right of hearings in Colombia based on the analysis of the figure of the ombudsman for viewers. [Methodology/Approach/Design] Legal, dogmatic, qualitative research, with a hermeneutic approach and documentary technique. Primary sources were used: regulations and jurisprudence, and secondary sources: specialized literature. These were traced in legal and academic databases, processed in files, and discussed by the research team. [Findings] The evidence of the existence of a right of hearings and the analysis of its objective dimension was developed. Its strong epistemological and dogmatic autonomy, its relative regulation autonomy, and its weak pedagogical autonomy are demonstrated. [Practical Implications] A more systematic regulation development of the right of hearings in the Colombian legal system is necessary. In turn, it is necessary to address other research areas that delve deeper into the most sensitive issues of the legal relationship between the media and viewers. The research contributes to the debate on the strengths and weaknesses of the democratic model in Colombia. [Originality] The research is innovative and original, given the absence of studies on the subject in Colombia.